Study of Living Law and its Implication in the Formation of the Criminal Code (KUHP) in the Era of Decentralization of Indonesian Laws - Zuwanda, Zulkham Sadat; Sopian, Sopian (West Science Law and Human Rights, 2024)
This study explores the implications of living law in the formation of Indonesia's Criminal Code during the era of legal decentralization. Living law, comprising unwritten customs and traditions, continues to play a vital role in many Indonesian communities, particularly in the context of criminal justice. The research employs a juridical analysis and case study approach, focusing on regions where adat law (customary law) significantly influences legal practices. The findings reveal both the benefits and challenges of integrating living law into the formal legal system. While living law enhances cultural relevance and community-based justice, it also introduces concerns about legal fragmentation and potential conflicts with national human rights standards. The study recommends selective incorporation of living law into the Criminal Code, along with efforts to codify regional customs to ensure consistency and legal certainty. This research contributes to the ongoing debate on legal pluralism in Indonesia, offering insights into the future of criminal law reform in a decentralized system.